Audit Committee Attributes and Firm Performance: Evidence from a Panel data analysis of Sri Lankan Listed Companies - Balagobei, S.; Parathan, S. (Wayamba University of Sri Lanka, 2019)
The Audit committee is the potential mechanism that reduces the principal and agent problems (agency problems) in organizations and investigating this mechanism separate from alternate corporate governance mechanisms may have led to different results in the literature. The purpose of this study is to empirically examine the impact of AC attributes on firm performance of listed companies in Sri Lanka. Firm performance is measured by Return on Assets (ROA) and Tobin's Q (TQ) while AC attributes consists AC size, AC independence, AC meetings and AC financial expertise. Sixteen listed companies in Colombo stock exchange were selected as the sample. In this study , data was collected from secondary sources and hypotheses are examined by using multiple regression analysis. The results reveal AC attributes such as AC size, and AC independence have a significant impact on both ROA and TQ, AC meeting and AC financial expertise are not found to have a significant impact on both ROA and TQ. AC meeting and AC financial expertise are not found to have a significant impact on firm performance.
Keywords: Audit committee; Audit committee financial expertise; Audit committee independence; Audit committee meetings; Audit committee size; Firm performance